A Meta Analisis Pengaruh Model PjBL terhadap Kemampuan Berpikir Kreatif Peserta Didik - Widyastuti, Rini; Jalinus, Nizwardi; Ridwan; Abdullah, Rijal; Krismadinata (The Indonesian Journal of Computer Science, 2024)
The Project Based Learning (PjBL) model is a learning strategy where students work on projects that help solve community/environmental problems. The ability to think at a higher level is a life skill that students must develop to face the challenges of life in the 21st century. One of the abilities at a high level is the ability to think creatively. The aim of this research is to analyze the effect of project-based learning on creative thinking skills. This research method is meta-analysis using a sample of 16 articles from various article sources. The research was conducted using quantitative methods using the OpenMEE application as a measure of effect size. The results of the meta-analysis show that the application of the PjBL model significantly influences students' creative thinking abilities as seen from various subjects and levels of education, from elementary school to college. The average effect size results are in the very high category, which means that the application of the PjBL model in learning influences creative thinking abilities